Late Triassic - Late Jurassic subsidence analysis in Neuquén Basin central area. (October 2019) - Scivetti, Nicolas; Franzese, Juan R.
Abstract: This paper presents a detailed study of the tectonic subsidence evolution during the Late Triassic - Late Jurassic period in the central area of the Neuquén Basin. The methodology consisted of the integration of outcrop and subsurface data, in order to obtain tectonic subsidence curves for the analyzed period in the study area. The origin of the basin was linked to a lithospheric mechanical extension episode in the Late Triassic - Early Jurassic that, once completed, gave rise to a post-rift stage. The post-rift stage, comprised between Early Jurassic and Early Cretaceous, was classically assumed as dominated by thermal subsidence. Results obtained in this paper show that there is a change in the geometry of the tectonic subsidence curves, which depart considerably from the expected behavior for a basin dominated by thermal subsidence. Therefore, the post-rift stage of the Neuquén Basin for the study area would have had a more complex tectonic evolution than that determined exclusively by the thermal subsidence, and that superposition of mechanisms must be considered. From the available data, a shift from thermal to dynamic subsidence from the Middle Callovian onwards seems to be the most plausible explanation for the subsidence evolution observed in the study area. Highlights: Backstripping was applied for Late Triassic - Late Jurassic period of Neuquén Basin. Obtained tectonic subsidence curves differs from thermal subsidence models. The accumulation of Lotena Group could have been controlled by dynamic subsidence.